Social research on transformation in developing countries: Results of interdisciplinary PhD-school participants - Mirka Dreger; Anke Huenninghaus (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2003)
This book is an attempt of documenting the results from interdisciplinary cooperation within the second intake of IEE's PhD-school from the viewpoint of the PhD-students. Under the above main heading of the school, students of this second cohort were working on the "Micro-Foundation of Macro-Processes of Economic, Legal and Social Reform" at their individual PhD-thesis. Six of those, all of them joining the school right at the beginning of the second intake, decided to systematically work out the value added of interdisciplinary cooperation in the PhD-school on the bases of their individual PhD-projects.
Keywords: 320; Systemtransformation; Demokratie; Verwaltungsreform; Sozialforschung; Entwicklungsländer